2015
DOI: 10.1111/cei.12576
|View full text |Cite
|
Sign up to set email alerts
|

Follicular T helper cells and humoral reactivity in kidney transplant patients

Abstract: Summary Memory

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
118
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(125 citation statements)
references
References 42 publications
7
118
0
Order By: Relevance
“…[5][6][7] The requirement of T-cell help for B-cell antibody production was first described in the late sixties. 8,9 CD4 Tfh cells of the secondary lymphoid organs are now recognized as the immune cells that are responsible for orchestrating the molecular interactions that provide help to B cells.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] The requirement of T-cell help for B-cell antibody production was first described in the late sixties. 8,9 CD4 Tfh cells of the secondary lymphoid organs are now recognized as the immune cells that are responsible for orchestrating the molecular interactions that provide help to B cells.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in the patients with chronic renal allograft rejection, increased circulating Tfh-cell ratio and decreased PD-1 expression were observed36. Furthermore, in the kidney biopsies taken during rejection, researchers found that the Tfh cells co-localized with CD20 + B cells and immunoglobulins in follicular-like structures, suggesting that Tfh cells might act as a bridge between cellular and humoral reactivity in acute rejection of kidney transplantation37.…”
Section: Discussionmentioning
confidence: 99%
“…Baan and colleagues examined the kidney biopsies that were obtained from recipients with ongoing renal allograft failure and found that Tfh cells and B cells co-localized (119), indicating Tfh cells could trigger alloantigen-specific antibody production by B cells. Using a mouse model of allogeneic hematopoietic stem cell transplantation, Blazar and colleagues revealed that Tfh cells are required for chronic graft-versus-host disease (cGVHD) in mice (120).…”
Section: Mainmentioning
confidence: 99%